Omental Infarction Mimicking Cholecystitis - David Smolilo; Benjamin C. Lewis; Marina Yeow; David I. Watson (Case Reports in Surgery)
Omental infarction can be difficult to diagnose preoperatively as imaging may be inconclusive and patients often present in a way that suggests a more common surgical pathology such as appendicitis. Here, a 40-year-old Caucasian man presented to casualty with shortness of breath and progressive right upper abdominal pain, accompanied with right shoulder and neck pain. Exploratory laparoscopy was eventually utilised to diagnose an atypical form of omental infarction that mimics cholecystitis. The vascular supply along the long axis of the segment was occluded initiating necrosis. In this case, the necrotic segment was adherent with the abdominal wall, a pathology not commonly reported in cases of omental infarction.